Production of anti-inflammatory and antidiabetic oligosaccharides from okra mucilage through one-step microbial fermentation - Ayaz Ahmad; Imdad Ullah Khan; Yusra Jamil; Aymen Ajmal; Murad Ali; Muhammad Ihtesham; Douglas Law; Patricio R. De los Ríos-Escalante; Saeedah Almutairi; Wahidah H. Al-Qahtani; Ahmed Othman Alsabih; Mostafa A. Abdel-Maksoud; et al. (PLoS ONE, 2026)
Plant-based natural products are increasingly being explored as safer and more sustainable alternatives than synthetic drugs for controlling globally rising chronic health conditions, including inflammation and diabetes. Microbial fermentation has long been used to enhance the value and bioactivity of natural products. In this study, we produced bioactive oligosaccharides from okra ( Abelmoschus esculentus ) mucilage polysaccharides using a sustainable one-step Pichia kudriavzevii -mediated fermentation approach. The oligosaccharide fractions separated by size-exclusion chromatography primarily contained uronic acids, pentoses, and hexoses. In vitro assays showed that these oligosaccharides possess notable anti-inflammatory and antidiabetic potential. Among the fractions, ODF91 exhibited the strongest membrane-stabilizing activity, providing 92.86% protection of the erythrocyte membrane, comparable to that of the standard anti-inflammatory drug. ODF91, at 200 mg/kg, markedly reduced paw edema by 94.69% in the carrageenan-induced mouse model, supporting preliminary in vivo anti-inflammatory activity. ODF91, at 200 mg/kg, also lowered blood glucose levels in streptozotocin-induced diabetic mice by 86.91%, followed by ODF83 and ODF84, suggesting promising preliminary antihyperglycemic activity. Furthermore, lipid profile parameters significantly improved in diabetic mice after treatment with these oligosaccharides. Collectively, these results suggest that the fermented okra-derived oligosaccharides possess promising anti-inflammatory and antidiabetic properties and highlight microbial fermentation as a scalable strategy for converting underutilized plant polysaccharides into value-added bioactive products.